Pasiones, pulsiones y deseo: amalgama fundamental de toda ética - Alzate Posada, Luz Stella (Nómadas. Critical Journal of Social and Juridical Science, 2009)
How is it made an ethics? Or more, which is the role of the passions, of the impulses and of the desire in the conformation of an ethics given, conceived like the foundation of any human conduct? This is the question to which you try giving un answer in this article from the Spinoza’s ethics until arriving to the Lacan’s desire, going of course through the Freud’s impulse. The dialog between these two depth knowledge of the human like they are the philosophy and the psychoanalysis it’s what will guide us in this task. Our tour will take us from Descartes to Spinoza and with them, from the passions of the soul to the Spinoza’s desire followed by the will and the ethics, and likewise to the impulses and to the Freud’s pleasure principle to conclude saying that the passions, the impulses and the desire are the fundamental amalgam of any ethics.